Evolution and Variation of the Yeast (Saccharomyces) Genome - Mortimer, Robert K.

(untitled) (Genome Research, 2000)
In this review we describe the role of the yeastSaccharomyces in the development of human societies including the use of this organism in the making of wine, bread, beer, and distilled beverages. We also discuss the tremendous diversity of yeast found in natural (i.e., noninoculated) wine fermentations and the scientific uses of yeast over the past 60 years. In conclusion, we present ideas on the model of “genome renewal” and the use of this model to explain the mode by which yeast has evolved and how diversity can be generated.